Prevalence of Sagittal Molar Relationship Among Iraqi Adolescents in Erbil City/Iraq - Mokhtar M. Sofyan Al-Hamidi; Dina Isam Afram Jarjur; Rana Ghaib Husamaddin (University of Mosul, College of Dentistry, 2022)
Aims: The aim of this study is to assess the prevalence of Angle's molar classification and recording sagittal malocclusion, among (15- 18) years-old-school students; by studying two factors: gender and the socio-economic status, which are represented by the school type as private or public schools. Materials and Methods: In this cross-sectional study, a total of 593 aged between 15 - 18 years old. Students were included from randomly selected male, female and mixed high schools. Distributed in different areas in Erbil city. Excluding those who previously had orthodontic treatment, orthognathic surgery, missing upper or lower first molar, and students with any contagious diseases. The molar relationship was determined by direct clinical examination according to Angle's classifications and sub-classifications. Statistical analysis was obtained using SPSS (Statistical Package for the Social Sciences). Pearson Chi-Square test was used to determine the significance among the data's variables. Results: The findings showed 90.2 % of the subjects had malocclusion, and the prevalence of malocclusion was as the following: Class I 59.1%, Class II 24.7%, Class III 16.2%, respectively. According to gender, Chi-square was significant in molar classification and sub-classification. As for the school type, Chi-square was not significant in molar classification, but it was significant in sub-classification at p-value ≤0.05. Conclusions: Malocclusion is relatively high in Erbil city among adolescents.